Maleic anhydride proton sponge as a novel MALDI matrix for the visualization of small molecules (<250 m/z) in brain tumors by routine MALDI ToF imaging mass spectrometry. Issue 63 (15th July 2016) - Giampà, M.; Lissel, M. B.; Patschkowski, T.; Fuchser, J.; Hans, V. H.; Gembruch, O.; Bednarz, H.; Niehaus, K.
Abstract : A novel MALDI matrix MAPS, able to visualize deviating metabolism in glioma using a routine MALDI-ToF-MSI procedure, is presented. Abstract : A novel vacuum stable proton sponge, 4-maleicanhydridoproton sponge (MAPS), was prepared and applied as the matrix in Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Imaging (MALDI-MSI) of an aggressive brain tumor tissue (glioblastoma multiforme). Ionic maps of lactate, 2-hydroxyglutarate and chloride anions ( m / z 89, 147, 35, respectively) were obtained using a routine MALDI ToF mass spectrometer.